2018
DOI: 10.1021/acsaelm.8b00034
|View full text |Cite
|
Sign up to set email alerts
|

An Optically Gated Transistor Composed of Amorphous M + Ge2Se3 (M = Cu or Sn) for Accessing and Continuously Programming a Memristor

Abstract: We demonstrate that a device composed of sputtered amorphous chalcogenide Ge 2 Se 3 /M + Ge 2 Se 3 (M = Sn or Cu) alternating layers functions as an optically gated transistor (OGT) and can be used as an access transistor for a memristor memory element. This transistor has only two electrically connected terminals (source and drain), with the gate being optically controlled, thus allowing the transistor to operate only in the presence of light (385−1200 nm). The switching speed of the OGTs is <15 μs. The OGT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Thus, GeSe 3 is a good demonstrator system, while other materials, such as ternary compositions and tellurides 51 , 56 may be better-suited for applications that will make use of the optical modulation in the visible and infrared. We also note that existing work has demonstrated the usefulness of the GeSe-based optically controlled memristors 14 , 57 , and products utilizing such optical programmability are already commercially available 58 . The cavity design and downscaling of devices shown in this work thus expand the utility of this emerging device concept for computing applications.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, GeSe 3 is a good demonstrator system, while other materials, such as ternary compositions and tellurides 51 , 56 may be better-suited for applications that will make use of the optical modulation in the visible and infrared. We also note that existing work has demonstrated the usefulness of the GeSe-based optically controlled memristors 14 , 57 , and products utilizing such optical programmability are already commercially available 58 . The cavity design and downscaling of devices shown in this work thus expand the utility of this emerging device concept for computing applications.…”
Section: Resultsmentioning
confidence: 91%
“…Consequently, a neuromorphic device with multi-factor in-memory processing would be highly impactful. A memristive approach that enables the interaction of two distinct signals, such as an electrical and an optical signal, could be a candidate for such a neuromorphic device 14 . Here we demonstrate such an electrical-optical dual-signaling framework, using germanium selenide (GeSe 3 ) memristive nano-cavities.…”
Section: Introductionmentioning
confidence: 99%
“…[27] In another work, K. Campbell et al reported a memristor that is light gated using a transistor structure based on sputtered amorphous chalcogenide Ge 2 Se 3 /M + Ge 2 Se 3 (M = Sn or Cu) alternating layers. [28] Multiple states can be programmed within the memristor with a switching speed of less than 15 µs. The programmed state is dictated by the applied light intensity which controls the saturation of the current level within the optically gated device.…”
Section: Accepted Articlementioning
confidence: 99%
“…[27] In another work, Campbell et al reported a memristor that is light gated using a transistor structure based on sputtered amorphous chalcogenide Ge 2 Se 3 /M þ Ge 2 Se 3 (M ¼ Sn or Cu) alternating layers. [28] Multiple states can be programmed within the memristor with a switching speed of less than 15 μs. The programmed state is dictated by the applied light intensity which controls the saturation of the current level within the optically gated device.…”
Section: In-memory Optical Sensing-optical Memsorsmentioning
confidence: 99%